Diseño y primera fase de implementación de un sistema de gestión ambiental basado en la norma ISO 14001 para la empresa Textiles del Valle S.A. - Duarte Rivera, Joselin Dayri (2015)
The current study presents the design and first implementation phase of an Environmental Management System, based on the ISO 14001: 2004 standard for the industry “Textiles Valle S.A.”, wich was developed in four chapters. In the first chapter, the definitions, objectives and requirements of the Environmental Management System are discussed. In chapter two the situation of the industry is exposed, highlighting its organization, industrial activities, products and services, it also contains the characterization of physical, biotic and socioeconomic medium that identifies the adjacent area, in addition to the initial environmental review. The development of procedures required by ISO 14001: 2004 is presented in chapter three, while the fourth chapter focuses on the first phase of implementation of the designed system, so it is possible to find the recognition of significant environmental aspects, the defined environmental policy, the identification of the legal requirements applicable to the nature of the industry, and the establishment of environmental objectives and targets.